Do serum vitamins, carotenoids, and retinyl esters influence mortality in osteoarthritis? Insights from a nationally representative study - Lu, Yifan; Duan, Junjie; You, Rong; Tang, Simin; Qi, Xinyu; Wu, Boyu; Jian, Gonghui; Wang, Tao; Duan, Jianhui; Yang, Zhuo (Frontiers in Nutrition, 2025)
BackgroundThe relationship between serum vitamins, carotenoids, and retinyl esters and mortality risk among individuals with osteoarthritis (OA) remains unclear. This study aimed to investigate these associations.MethodsBased on data from NHANES 2001 to 2018 and the National Death Index (NDI), a total of 3,626 patients with OA were included. Cox proportional hazards models were used to evaluate the associations between serum nutrient levels and all-cause, cardiovascular, and cancer mortality. Nonlinear effects were assessed using smooth curve fitting and piecewise regression models. Subgroup analyses, sensitivity analyses, and validation in non-OA populations were conducted. Additionally, interactions between vitamin levels and OA status were examined.ResultsHigher levels of vitamin D, retinyl palmitate, and stearic acid were associated with a reduced risk of all-cause mortality in patients with OA, with consistent results in sensitivity analyses. A nonlinear inverse association was observed between vitamin D and all-cause mortality in women, with a threshold at 30.5 nmol/L. Vitamin C was associated with cardiovascular mortality, while retinyl palmitate and stearic acid were linked to a reduced risk of cancer-related death. The protective effect of vitamin D was stronger among individuals with lower educational levels. In the non-OA population, only vitamin D was associated with mortality. Interaction analysis indicated that high vitamin levels may attenuate the adverse impact of OA on mortality risk.ConclusionsElevated serum levels of vitamin D, retinyl palmitate, and stearic acid may be associated with reduced all-cause and cause-specific mortality among individuals with OA, highlighting their potential role in the management of OA.